Automatic satellite tracking system on a movable platform - Ili Hazwani Zakaria (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
Satellite dish antennas have become popular in recent years primarily for use in-vehicle communication systems. Accordingly, the satellite dish antenna further comprises a roof mount to install the dish on the roof of the vehicle, such as maritime vessel, truck, or caravan. However, such a mobile satellite dish has several drawbacks. As it is mentioned above, since the satellite dish antenna is a highly directional antenna, the dish must be manually adjusted its orientation when the vehicle travels from place to place. The tuning process requires the user to manually elevate, lower, and position the dish to the direction of the satellite, where the alignment of the dish is somewhat difficult to be fixed due to the manual adjustment and usually resulted in low-quality signal reception and possible satellite interference. Furthermore, the dish may be unintentionally shifted its orientation misalign with the direction satellite in a high wind operating environment. An automated satellite TV tracking system can rather be very expensive depending on system complexity. The mobile satellite dish antennas are costly to manufacture, install, and maintain in order to perform as the mentioned condition. Accordingly, the manufacture of the receiving dish itself is somewhat inexpensive. However, the installation of the satellite dish antenna is time-consuming and requires an experienced technician to install and maintain the whole electrical wiring for the user's requirements and the system's safety. This project is aimed to produce a reliable and cheaper prototype of satellite TV tracker system. The output of this project is intended to be mounted on a maritime vessel. The tracking of the satellite TV signal is difficult to achieve as the vessel is always in motion on the sea surface. Thus, this research presents the study, design and development of positioning control for the satellite tracking system on a maritime vessel. A stable satellite tracking controller by the module of combining Arduino microcontroller and accelerometer is designed to cope with the sensor imprecision and sea environment. DC motors are then used to move the satellite television dish according to the input of azimuth and elevation angles. The determination of where the motor should stop was achieved with the integration of a control system operated by Arduino programming and accelerometer sensor. The desired television signal can be brought to the TVRO on the mobile vessel through the antenna with the inputs orientation and the tracking controller. This information will depend on the latitude and longitude of the vessel's current position. The designed prototype is capable to track MEASAT 3B signal automatically using the programmable language. Hence, the signal gain is validated using a spectrum analyzer at any specific location to confirm and measure the signal strength of the TVRO which is more than the allowable minimum performance of the received satellite signal (≥ -31.987dBm). The accuracy of the tracker is measured within the allowable performance. Keywords: Satellite Tracker, DC Motors, Automatic Controller